Variations in Early Response of Grapevine Wood Depending on Wound and Inoculation Combinations with Phaeoacremonium aleophilum and Phaeomoniella chlamydospora - Pierron, Romain J. G.; Pouzoulet, Jérôme; Couderc, Christel; Judic, Elodie; Compant, Stéphane; Jacques, Alban (Frontiers in Plant Science, 2016)
Defense mechanisms in woody tissue are poorly understood, especially in vine colonized by trunk pathogens. However, several investigations suggest that molecular mechanisms in the central tissue of Vitis vinifera L. may be involved in trunk-defense reactions. In this work, the perception of Phaeoacremonium aleophilum and Phaeomoniella chlamydospora alone or together were investigated in cuttings of Cabernet Sauvignon trunks. Plant responses were analyzed at the tissue level via optical microscopy and at the cellular level via plant-gene expression. The microscopy results revealed that, six weeks after pathogen inoculation, newly formed vascular tissue is less developed in plants inoculated with P. chlamydospora than in plants inoculated with P. aleophilum. Co-inoculation with both pathogens resulted in an intermediate phenotype. Further analysis showed the relative expression of the following grapevine genes: PAL, PR10.3, TL, TLb, Vv17.3, STS, STS8, CWinv, PIN, CAM, LOX at 10, 24, 48, and 120 h post-inoculation (hpi). The gene set was induced by wounding before inoculation with the different pathogens, except for the genes CAM and LOX. This response generated significant noise, but the expression of the grapevine genes (PAL, PR10.3, TL, TLb, Vv17.3, STS, STS8, CWinv, and PIN) still differed due to perception of mycelium by the plant. Furthermore, at 48 hpi, the induction of PAL and STS8 differs depending on the pathogen, and a specific pattern emerges from the different inductions associated with the different treatments. Based on these results, we conclude that Vitis vinifera L. trunk perceives the presence of pathogens differently depending on the inoculated pathogen or even on the combination of co-inoculated pathogens, suggesting a defense orchestration in the perennial organs of woody plants.